PENGARUH KOMITMEN PROFESIONAL, LINGKUNGAN ETIKA, INTENSITAS MORAL, PERSONAL COST TERHADAP INTENSI UNTUK MELAKUKAN WHISTLEBLOWING INTERNAL (STUDI EMPIRIS PADA OPD KABUPATEN BENGKALIS) - Adhitya Agri Putra; Eka Hariyani (Jurnal Akuntansi Keuangan dan Bisnis, 2018)
This study aims to test and prove empirically: (1) Influence Professional commitment to intention to conduct internal whistleblowing (2) Environmental Effect of Intention to conduct internal whistleblowing (3) Effect of Moral Intensity on intention to conduct internal whistleblowing. (4) The influence of Personal Cost on the intention to conduct internal whistleblowing. The sample of this research is 124 people from 31 Organization of Regional Area of ​​Bengkalis Regency. The method of analysis in this study is multiple regression analysis. The results of this study indicate that (1) The professional commitment influences the intention to conduct an internal whistleblowing (2) The ethics environment affects the intention to conduct internal whistleblowing (3) Moral Intensity affects the intention to conduct internal whistleblowing (4) Personal Cost affects the intention to doing internal whistleblowing Keywords: Internal Whistleblowing Intent, Professional Commitment,Ethical Environment , Mental Intensity, Personal cost.